2022
DOI: 10.1177/15280837221121935
|View full text |Cite
|
Sign up to set email alerts
|

The hybridization effect and damage sequence investigation of biaxial/unidirectional braided composite tubes by micro-CT method

Abstract: Thanks to the 2D braiding manufacturing method, the hybrid braided composite composed of the biaxial and unidirectional layers is available in a mass-production manner. For enhancing the crashworthiness of braided composite tubes, the damage characteristics and energy absorption capacity of braided composite with biaxial/unidirectional hybridization structures under axial compression were studied in this work. The axial compression tests were conducted on pure biaxial and unidirectional braided tubes (BBB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The fiber volume fraction of carbon fiber/epoxy composites was measured by a burn‐off test approach 22 . By burning off all the matrix through the approach in a muffle furnace at 650°C, the fiber volume fraction can be determined 23 . The measured fiber volume fraction was displayed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fiber volume fraction of carbon fiber/epoxy composites was measured by a burn‐off test approach 22 . By burning off all the matrix through the approach in a muffle furnace at 650°C, the fiber volume fraction can be determined 23 . The measured fiber volume fraction was displayed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…22 By burning off all the matrix through the approach in a muffle furnace at 650 C, the fiber volume fraction can be determined. 23 The measured fiber volume fraction was displayed in Table 1.…”
Section: Materials 21 | Structural Characteristics Of Reinforcementsmentioning
confidence: 99%
“…Research has also shown that the braiding angle in braided composite cylinders has a considerable influence on the fracture behavior and failure modes created under different loadings. [21][22][23][24] Gu et al 3 investigated the torsion progressive damage and failure mechanism of two-dimensional (2D) braided carbon/epoxy composite cylinders with four braiding angles including; 30 , 45 , 55 , and 60 . They used three-dimensional digital image correlation to monitor the crack propagation and progressive torsional strain.…”
Section: Introductionmentioning
confidence: 99%
“…They used common strain gauges to carry out strain measurements without any discussion on strain distribution over the braid. Research has also shown that the braiding angle in braided composite cylinders has a considerable influence on the fracture behavior and failure modes created under different loadings 21–24 . Gu et al 3 investigated the torsion progressive damage and failure mechanism of two‐dimensional (2D) braided carbon/epoxy composite cylinders with four braiding angles including; 30°, 45°, 55°, and 60°.…”
Section: Introductionmentioning
confidence: 99%